Análise Linguística de Comentários de Humanos e de Modelos de Linguagem a Postagens em Comunidades Brasileiras do Reddit - Tobias, Fernanda Luiza; Silva, Ana Paula Couto da (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2025)
In this work, we analyze the linguistic differences between comments written by humans and those generated by large language models in social support communities on Reddit. Overall, the models tend to better align with the semantic content and linguistic style of the posts and are generally more informative, but their responses are often repetitive and harder to read. In contrast, human comments are typically more concise, diverse, and include personal experiences. Additionally, differences across communities suggest that the type of support being sought influences writing patterns.